Successful treatment of acquired hemophilia A associated with immune thrombocytopenia and joint hemarthrosis: A case report and literature review. Issue 38 (September 2018) - Wei, Fang
Abstract: Introduction: Acquired hemophilia A (AHA) is a rare bleeding disease caused by autoantibodies against factor VIII (FVIII). Spontaneous bleeding symptoms usually affect the skin, musco, muscle, and internal organs, while joint hemarthrosis in AHA is an extremely rare manifestation. AHA may have an autoimmune cause and is often associated with autoimmune disease, but no demonstrable platelet impairment was found in AHA patients. We report a patient with AHA complicated with a right shoulder joint hemarthrosis and immune thrombocytopenia. The patient was treated with fresh frozen plasma (FFP) and human prothrombin complex concentrate (hPCC) to control the active bleeding. Simultaneously this patient firstly accepted cyclophosphamide combined with prednisone to eradicate the inhibitor, while the treatment effect of cyclophosphamide combined with prednisone was not satisfactory. At last, she was successfully treated through the use of an anti-CD20 monoclonal antibody. Conclusion: AHA is an autoimmune disease and can co-exist with immune cytopenia besides connective tissue disease (CTD). Joint hemarthrosis is not specific to congenital hemophilia and mainly related to the extent of prolonged aPTT and weight loading of joint in AHA. When the first-line therapy of cyclophosphamide combined with prednisone is not enough to eradicate the inhibitor, especially for a higher inhibitor titer, anti-CD20 monoclonal antibody could play an important role.